The MSIS-29 and SF-36 as outcomes in secondary progressive MS trials. (September 2022) - Strijbis, Eva MM; Repovic, Pavle; Mostert, Jop; Bowen, James D; Uitdehaag, Bernard MJ; Cutter, Gary; Koch, Marcus W
Background: Patient-reported outcome measures (PROMs) are often used in clinical research, but little is known about their performance as longitudinal outcomes. Methods: We used data from ASCEND, a large SPMS trial ( n  = 889), to investigate changes on the Short Form Health Survey 36 (SF-36 v2) and the Multiple Sclerosis Impact Scale (MSIS-29) over 2 years of follow-up. Results: PROM scores changed little over the 2 years of follow-up. In contrast to physical disability measures, there was no consistent trend in PROM change: significant worsening occurred about as often as improvement. Using a 6-month confirmation reduced the number of both worsening and improvement events without altering their relative balance. There was no clear difference in worsening events in groups based on population characteristics, nor was there a noticeable effect using different thresholds for clinically significant change. Conclusion: We found little consistent change in MSIS-29 and SF-36 over 2 years of follow-up in people with SPMS. Our findings show a disconnect between disability worsening and PROM change in this population. Our findings raise caution about the use of these PROMs as primary outcome measures in SPMS trials and call for a critical reappraisal of the longitudinal use of these measures in SPMS trials.